Resonant acoustic rheometry for non-contact characterization of viscoelastic biomaterials. (February 2021) - Hobson, Eric C.; Li, Weiping; Juliar, Benjamin A.; Putnam, Andrew J.; Stegemann, Jan P.; Deng, Cheri X.
Abstract: Resonant Acoustic Rheometry (RAR) is a new, non-contact technique to characterize the mechanical properties of soft and viscoelastic biomaterials, such as hydrogels, that are used to mimic the extracellular matrix in tissue engineering. RAR uses a focused ultrasound pulse to generate a microscale perturbation at the sample surface and tracks the ensuing surface wave using pulse-echo ultrasound. The frequency spectrum of the resonant surface waves is analyzed to extract viscoelastic material properties. In this study, RAR was used to characterize fibrin, gelatin, and agarose hydrogels. Single time point measurements of gelled samples with static mechanical properties showed that RAR provided consistent quantitative data and measured intrinsic material characteristics independent of ultrasound parameters. RAR was also used to longitudinally track dynamic changes in viscoelastic properties over the course of fibrin gelation, revealing distinct phase and material property transitions. Application of RAR was verified using finite element modeling and the results were validated against rotational shear rheometry. Importantly, RAR circumvents some limitations of conventional rheology methods and can be performed in a high-throughput manner using conventional labware. Overall, these studies demonstrate that RAR can be a valuable tool to noninvasively quantify the viscoelastic mechanical properties of soft hydrogel biomaterials.